Crocetin as New Cross-Linker for Bioactive Sericin Nanoparticles - Sara Perteghella; Giovanna Rassu; Elisabetta Gavini; Antonella Obinu; Elia Bari; Delia Mandracchia; Maria Cristina Bonferoni; Paolo Giunchedi; Maria Luisa Torre (Pharmaceutics, 2021)
The nose-to-brain delivery route is used to bypass the blood–brain barrier and deliver drugs directly into the brain. Over the years, significant signs of progress have been made in developing nano-drug delivery systems to address the very low drug transfer levels seen with conventional formulations (e.g., nasal solutions). In this paper, sericin nanoparticles were prepared using crocetin as a new bioactive natural cross-linker (NPc) and compared to sericin nanoparticles prepared with glutaraldehyde (NPg). The mean diameter of NPc and NPg was about 248 and 225 nm, respectively, and suitable for nose-to-brain delivery. The morphological investigation revealed that NPc are spherical-like particles with a smooth surface, whereas NPg seem small and rough. NPc remained stable at 4 °C for 28 days, and when freeze-dried with 0.1% w/v of trehalose, the aggregation was prevented. The use of crocetin as a natural cross-linker significantly improved the in vitro ROS-scavenging ability of NPc with respect to NPg. Both formulations were cytocompatible at all the concentrations tested on human fibroblasts and Caco-2 cells and protected them against oxidative stress damage. In detail, for NPc, the concentration of 400 µg/mL resulted in the most promising to maintain the cell metabolic activity of fibroblasts higher than 90%. Overall, the results reported in this paper support the employment of NPc as a nose-to-brain drug delivery system, as the brain targeting of antioxidants is a potential tool for the therapy of neurological diseases.